High Glucose Suppresses Keratinocyte Migration Through the Inhibition of p38 MAPK/Autophagy Pathway - Li, Lingfei; Zhang, Junhui; Zhang, Qiong; Zhang, Dongxia; Xiang, Fei; Jia, Jiezhi; Wei, Ping; Zhang, Jiaping; Hu, Jiongyu; Huang, Yuesheng (Frontiers in Physiology, 2019)
Wound healing is delayed frequently in patients with diabetes. Proper keratinocyte migration is an essential step during re-epithelialization. Impaired keratinocyte migration is a critical underlying factor responsible for the deficiency of diabetic wound healing, which is mainly attributed to the hyperglycemic state. However, the underlying mechanisms remain largely unknown. Previously, we demonstrated a marked activation of p38/mitogen-activated protein kinase (MAPK) pathway in the regenerated migrating epidermis, which in turn promoted keratinocyte migration. In the present study, we find that p38/MAPK pathway is downregulated and accompanied by inactivation of autophagy under high glucose (HG) environment. In addition, we demonstrate that inactivation of p38/MAPK and autophagy result in the inhibition of keratinocyte migration under HG environment, and the activating p38/MAPK by MKK6(Glu) overexpression rescues cell migration through an autophagy-dependent way. Moreover, diabetic wound epidermis shows a significant inhibition of p38/MAPK and autophagy. Targeting these dysfunctions may provide novel therapeutic approaches.